Diets rich in n-3 polyunsaturated fatty acids are associated with amelioration of D-Galactosamine induced hepatitis in mice - Ramaballav Roy, Priyadarshini Dattatraya Pujari (Recent Research in Science and Technology, 2010)
Liver disorders are often associated with long chain polyunsaturated fatty acid deficiency due to hepatic insufficiency or lack of dietary intake that is hypothesized to further aggravate the condition. Consumption of diets rich in n-3 polyunsaturated fatty acids (PUFA) have been described to be beneficial against diets rich in saturated fatty acids (SFA) in various inflammatory disorders. Hence, we tested the hypothesis that the consumption of dietary fatty acids especially n-3PUFA is associated with the amelioration of hepatitis. We selected two sources of dietary fatty acids i.e. fish oil rich in n-3 PUFAÃ‚Â and meat oil rich in SFA. The diet preparation differed only in the type of the oil used. 10% fish oil or meat oil was freshly blended with the pellet diet and fed to the experimental mice for a period of 30 days. Hepatitis was induced in the experimental model i.e. mice (Mus musculus) by intraperitoneal injection of D-Galactosamine. Upon induction of hepatitis, the n-3 PUFA group showed elevated levels of total protein while maintaining thiobarbituric acid reactive substances and tocopherol unaltered. In contrast, the SFA group showed decreased level of total protein, reduced glutathione and tocopherol along with an augmentation of TBARS. Degree of augmentation of gamma glutamyl transpeptidase activity and bilirubin concentration upon induction of hepatitis were much lower in the fish oil supplemented groups compared to the control diet fed groups. In spite of induction of hepatitis, the n-3 PUFA group showed well preserved liver architechture with no evidence of hemorrhage, necrosis or hepatocytolysis except mild inflammation. Our present findings indicate a significant alleviation of D-GaIN induced hepatitis by dietary n-3 polyunsaturated fatty acids rich fish oil than that of meat oil.